Real-World Treatment Patterns and Outcomes of Growth Hormone Treatment Among Children in Israel Over the Past Decade (2004–2015) - Ben-Ari, Tal; Chodick, Gabriel; Shalev, Varda; Goldstein, Dalit; Gomez, Roy; Landau, Zohar (Frontiers in Pediatrics, 2021)
Objective: To assess a decade of growth hormone (GH) treatment patterns and outcomes in a real-world setting in Israel using a state-of-the-art computerized database. Methods: This large retrospective database study included 2,379 children initiating GH treatment in Maccabi Healthcare Services (between January 2004 and December 2014). Good adherence with therapy (proportion of days covered >80%) was assessed during follow-up. Results: At GH treatment initiation: 62.1% were boys; height standard deviation score (SDS) was –2.36±0.65 (mean±SD); age was 9.8±3.1 years; and time from short stature diagnosis to first GH purchase was 4.8±3.3 years. Mean treatment period was 3.5±0.95 years; 79.4% of children were treated for more than 3 years. The two main indications for GH therapy were idiopathic short stature (ISS) (n=1,615, 67.9%) and GH deficiency (GHD) (n=611, 25.7%). Children in the highest socio-economic-status (SES) tertile comprised 61.3% of ISS and 59.7% of GHD. After 3 years, mean height gain SDS was 1.09±0.91 for GHD and 0.96±0.57 for ISS (p=0.0004). Adult height (age 15 for girls and 17 for boys) was recorded for 624 patients (26.2%) with better outcomes for GHD than ISS (–1.0±0.82 versus –1.28±0.93, respectively; p=0.0002). Good adherence was achieved in 78.2% of the cohort during the first year and declined thereafter to 68.1% during the third year of the treatment. Conclusions: Children who initiate GH therapy are predominantly male, belong mainly to the upper SES, commence treatment a long period after initial recognition of short stature, and have suboptimal adherence. Appropriate referral, diagnosis, and follow-up care may result in better treatment outcomes with GH therapy.